I need to be in control: Motivations to compensate personal control threat through hierarchy endorsement among individuals with low vs. high relational mobility - ONG, Lay See (Institutional Knowledge at Singapore Management University, 2015)
Recent research on compensatory control indicate a motivation seek out external sources of control (e.g., hierarchical structures) when subjective control is threatened. As exiting/formation of interpersonal relationships within low relational mobility environments is likely to be beyond personal choice and may threaten subjective control, three studies were conducted to investigate whether the compensatory control account could explain the negative relationship found between hierarchy endorsement and low relational mobility. Study 1 provided initial evidence for the link; low personal-low environmental mobility individuals (vs. high personal-high environment mobility participants) were more likely to indicate higher internal control when they had higher (.vs lower) hierarchy endorsement. Study 2 and Study 3 extended Study 1 by showing (a) the different patterns of percieved internal control gain among high and low relational mobility individuals after hierarchy exposure (Study 2), and (b) how a macro-level threat (i.e., system threat) moderates the compensatory control phenomenon among high and low relational mobility individuals (Study 3). Altogether, the studies inform us of how social ecology and individual experiences may interact to influence the individual psyche.